THE INFLUENCE OF IMPLEMENTING QUALITY MANAGEMENT TOWARDS PURCHASING PERFORMANCE AND COMPETITIVE ADVANTAGE MAKING - Meirani Harsasi; Fahmy Radhi (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
This study examined the effect of quality management practices on purchasing performance and competitive advantage. The data were collected through questionnairesconsisting of 152 manufacturing companies in West Java, by using purposive sampling method. The hypotheses were tested by using Structural Equation Modeling (SEM.)The results indicate that quality management practices in purchasing had significant influence on purchasing performance, while quality performance had also significantinfluance on competitive advantage. Another finding was that quality management practices in purchasing had significant influence on the quality performance mediated bypurchasing performance. Keywords: quality management practices in purchasing, purchasing performance, qualityperformance, competitive advantage